A Practical Handbook for Environmental Regulators and Legislators Working in Situations Affected by Fragility, Conflict and Extreme Violence - Pohl, Wolfhart; Humphry, Ella (World Bank, Washington, DC, 2016)
This handbook is the product of a workshop held in June 2014 with about 25 environmental regulators from over 10 FCV-affected countries (Burkina Faso, Central African Republic, Kenya, Liberia, Madagascar, Mali, Mozambique, Nigeria, Sierra Leone, South Sudan, and Sudan) that was financed by the Korean Trust Fund (KTF) and organized and hosted by the World Bank Group (WBG). Over the course of one week the participants went through a dense program consisting of presentations, discussions, participatory exercises, field trips and the preparation and presentation of case studies from their own countries. The materials processed and harvested during the workshop were extremely rich, and it seemed logical to capture them in a form that will be of continued practical use for the participants. This handbook is intended as a handy toolkit with practical tips that is borne out of experiences garnered from years of working in FCS, including post conflict situations. The structure of this handbook was conceived during extensive discussions towards the end of the workshop and seen as a ‘road map’ towards the best chance for environmental regulators to make a difference in practice.